2009
DOI: 10.1016/j.neuron.2009.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Subunit Composition of Synaptic AMPA Receptors Revealed by a Single-Cell Genetic Approach

Abstract: Summary The precise subunit composition of synaptic ionotropic receptors in the brain is poorly understood. This information is of particular importance with regard to AMPA-type glutamate receptors, the multimeric complexes assembled from GluA1-A4 subunits, as the trafficking of these receptors into and out of synapses is proposed to depend upon the subunit composition of the receptor. We report a molecular quantification of synaptic AMPA receptors (AMPARs) by employing a single-cell genetic approach coupled w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

50
573
3
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 565 publications
(638 citation statements)
references
References 82 publications
(138 reference statements)
50
573
3
1
Order By: Relevance
“…The ionotropic glutamate receptor family comprises the AMPA, kainate and NMDA receptors, which mediate most excitatory neurotransmission in the central nervous system and function by opening a transmembrane ion channel on binding of glutamate (Lu et al, 2009). The AMPA receptor subfamily forms functional heterotetramers composed of four types of subunits, designated GluR1 (GRIA1), GluR2 (GRIA2), GluR3 (GRIA3) and GluR4 (GRIA4), whereas the AMPA receptor activity is largely dependent on the AMPA receptor composition and in particular on the presence and processing of the GluR2 subunit.…”
Section: Introductionmentioning
confidence: 99%
“…The ionotropic glutamate receptor family comprises the AMPA, kainate and NMDA receptors, which mediate most excitatory neurotransmission in the central nervous system and function by opening a transmembrane ion channel on binding of glutamate (Lu et al, 2009). The AMPA receptor subfamily forms functional heterotetramers composed of four types of subunits, designated GluR1 (GRIA1), GluR2 (GRIA2), GluR3 (GRIA3) and GluR4 (GRIA4), whereas the AMPA receptor activity is largely dependent on the AMPA receptor composition and in particular on the presence and processing of the GluR2 subunit.…”
Section: Introductionmentioning
confidence: 99%
“…Immuno-gold staining and electron microscopy studies have estimated that GluA3 is present at only ~10% of GluA1 or GluA2 levels 7 . Moreover, single cell deletion studies reported that ~80% of synaptic AMPARs in CA1 hippocampal neurons comprise GluA1/GluA2 hetromers 8 . However, other studies of subunit abundance in rat hippocampus and cortex suggest AMPARs comprise mainly heteromers containing GluA1 and GluA2 or GluA2 and GluA3 [8][9][10] with approximately equivalent amounts of each heteromer complex 11 .…”
Section: Subunit-specific Traffickingmentioning
confidence: 99%
“…Moreover, single cell deletion studies reported that ~80% of synaptic AMPARs in CA1 hippocampal neurons comprise GluA1/GluA2 hetromers 8 . However, other studies of subunit abundance in rat hippocampus and cortex suggest AMPARs comprise mainly heteromers containing GluA1 and GluA2 or GluA2 and GluA3 [8][9][10] with approximately equivalent amounts of each heteromer complex 11 . GluA4, on the other hand is tightly developmentally regulated and is sparsely expressed at glutamatergic synapses in principal neurons in adult brain 12 .…”
Section: Subunit-specific Traffickingmentioning
confidence: 99%
“…In the adult hippocampus, the AMPAR consists mainly of GluA1/GluA2 and, to a lesser extent, GluA2/GluA3 hetero-tetramers 34 . GluA1 mediates activity-dependent synaptic targeting and removal of the AMPAR during LTP 17, 19 and LTD 14 , in part through phosphorylation and dephosphorylation of its cytoplasmic domain 35 .…”
Section: Pleiotropic Effects Of Stim2 On Glua1 Traffickingmentioning
confidence: 99%